Pelatihan Penyegaran Prinsip Akuntansi untuk Akuntan di PT Anugrah Argon Medica dengan Model GOAD - Astrid Rudyanto; Suryanto; Kartina Natalilova; Widyawati Lekok; Apit Susanti; Yohanes (Universitas Muhammadiyah Palembang, 2024)
This community service program aims to offer a fundamental accounting refresher to accountants at a prominent distribution company in Indonesia (PT Anugrah Argon Medica) with GOAD model. This practice aims to reinforce their comprehensive understanding of journal logic and its influence on financial accounts and their interpretation. Every accountant must possess a comprehensive understanding of fundamental accounting principles to accurately prepare journals and comprehend the effect of each journal entry on the components of the financial statements, especially in distribution companies. This community service initiative is aimed at all accounting personnel in PT Anugrah Argon Medica. This community service project occurred over seven days, specifically from August 15 to August 28, 2024, at the company's headquarters. Community service activities commenced with an introduction to normal balances, the creation of general journals, the adjustment of journals, and the preparation of financial statements. Quantitative and qualitative test results indicated an enhancement in employees' fundamental accounting skills following the training session.